Retrieval and Encoding Interference: Cross-Linguistic Evidence from Anaphor Processing - Laurinavichyute, Anna; Jäger, Lena A.; Akinina, Yulia; Roß, Jennifer; Dragoy, Olga (Frontiers in Psychology, 2017)
The main goal of this paper was to disentangle encoding and retrieval interference effects in anaphor processing and thus to evaluate the hypothesis predicting that structurally inaccessible nouns (distractors) are not considered to be potential anaphor antecedents during language processing (Nicol and Swinney, 1989). Three self-paced reading experiments were conducted: one in German, comparing gender-unmarked reflexives and gender-marked pronouns, and two in Russian, comparing gender-marked and -unmarked reflexives. In the German experiment, no interference effects were found. In the first experiment in Russian, an unexpected reading times pattern emerged: in the condition where the distractor matched the gender of the reflexive's antecedent, reading of the gender-unmarked, but not the gender-marked reflexives was slowed down. The same reading times pattern was replicated in a second experiment in Russian where the order of the reflexive and the main verb was inverted. We conclude that the results of the two experiments in Russian are inconsistent with the retrieval interference account, but can be explained by encoding interference and additional semantic processing efforts associated with the processing of gender-marked reflexives. In sum, we found no evidence that would allow us to reject the syntax as an early filer account (Nicol and Swinney, 1989).